2022
DOI: 10.1097/bor.0000000000000923
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in osteoarthritis: the latest progress and ongoing challenges

Abstract: Purpose of reviewThe understanding of inflammation in osteoarthritis is rapidly evolving. This review highlights important basic science, mechanistic, and clinical findings since 2020 that underscore the current notion of osteoarthritis as an inflammatory disease.Recent findingsThere exists a disconnect between clinical radiographic findings and patient symptoms in osteoarthritis. Inflammation, in particular synovitis, has been put forward as a potential explanation for this disconnect. New findings have shed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…In particular, severe oxidative stress may cause inflammation through the activation of the NF‐κB pathway 43 . NF‐κB, which is a primary regulatory factor in the expression of inflammation‐related cytokines and mediators, could be activated by LPS stimulation in macrophages 13,44,45 . Therefore, we further investigated the effect of BR on NF‐κB activation.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, severe oxidative stress may cause inflammation through the activation of the NF‐κB pathway 43 . NF‐κB, which is a primary regulatory factor in the expression of inflammation‐related cytokines and mediators, could be activated by LPS stimulation in macrophages 13,44,45 . Therefore, we further investigated the effect of BR on NF‐κB activation.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the adoption of open surgery which exposes the joint cavity increases the risk of bleeding and inflammation in the joint cavity compared to minimally invasive arthroscopic surgery. This causes an imbalance in the intra‐articular environment and secondary destruction of articular cartilage [14]. The open procedure destroys MCL, normal postoperative activity of the rabbit can cause laxity of the sutured MCL, which in turn triggers instability of the knee joint and degeneration of the articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…1). 34,35 Given that BME is a nonspecific finding, it is predictable that previous studies have shown young athletes with BME in the absence of symptomatology. 36,37 One could argue that the studies were cross sectional at a specific point in time and lacked longitudinal follow-up after the emergence of ELMSI.…”
Section: Pathophysiology Of Elmsi In Relation To Pain Generatormentioning
confidence: 99%